Clinical MR Imaging A Practical Approach - Reimer, Peter; Parizel, Paul M.; Meaney, James F.M; Stichnoth, Falko-Alexander (Springer Berlin Heidelberg : Imprint: Springer, 2010)
Magnetic resonance imaging (MRI) has become the leading cross-sectional imaging method in clinical practice. Continuous technical improvements have significantly broadened the scope of applications. At present, MR imaging is not only the most important diagnostic technique in neuroradiology and musculoskeletal radiology, but has also become an invaluable diagnostic tool for abdominal, pelvic, cardiac, breast and vascular imaging. This book offers practical guidelines for performing efficient and cost-effective MRI examinations in daily practice. The underlying idea is that, by adopting a practical protocol-based approach, the work-flow in a MRI unit can be streamlined and optimized.